Copper(I) Sulfide - Iron(II,III) Oxide Nanocomposite Assisted Treatment for the Removal of Lead from Domestic Wastewater - Kocoglu, Elif Seda; Serbest, Hakan; Bakirdere, Sezgin (TAYLOR & FRANCIS INC, 2026)
The removal of toxic elements/metals from contaminated water is critical due to their effects on human health/environment. Lead contamination in water sources has been linked to a range of health issues, as well as environmental degradation. This study introduces a novel strategy for efficiently removing lead ions from synthetic domestic wastewater using a Cu2S@Fe3O4 nanocomposite as an adsorbent. The removal efficiency of developed method was systematically evaluated after optimization of various experimental parameters including pH, buffer volume, adsorbent dosage, and mixing type and period. The removal efficiencies were calculated between 65% and 98% for different concentrations under optimum experimental conditions summarized as 20 mL of sample, 0.50 mL volume of pH 6.0 buffer, 60 mg of Cu2S@Fe3O4 nanocomposites, and 45 s of vortexing. Three linearized adsorption isotherm models including Langmuir, Freundlich, and Temkin were used to assess the equilibrium data. Moreover, the adsorption kinetics were found to be in good agreement with the pseudo-second order kinetic model. The obtained data supports the applicability of the proposed method as a good alternative for the removal of lead from wastewater matrices with high removal efficiency.
Keywords: Adsorption; copper(I) sulfide - iron(II,III) oxide nanocomposite; flame atomic absorption spectrometry (FAAS); isotherm models; lead; synthetic wastewater; AQUEOUS-SOLUTION; NANOPARTICLES; IONS; PB(II); Chemistry